Assessing economic sustainability of Malaysian rice farming (1972-2014) - Mohd Nor, K. N.; Arumugum, Nalini; Abdullah, Adam; Tening Pahang, Josephine (Universiti Teknologi MARA (UiTM), 2018)
The recent focus of agricultural planning is on sustainable development which is very pertinent to Malaysian rice industry. Therefore, this study intends to assess the long term economic sustainability of Malaysian rice farming (1972-2014), by reviewing the bottom line of prices and the purchasing power of rice (PPR). Statistical information of time series data on farm harvest price of rice (PR), wholesale commodity price (WP) and rice production for 42 years period was obtained and compiled from the AGROSTAT system of the statistical division of the Food and Agriculture Organization (FAO), the United States Department of Agriculture (USDA), World Bank and the Department of Statistics, Malaysia. The data was analysed using Abdullah’s analysis of the impact of changes the value and purchasing power of money and wheat in real terms (2013, p.71). The outcome reveals that the PR follows the general price trend in commodities, even with increased productivity. Thus, the index value of PR in 2014 at 375% of 1972 prices and WP generally at 614%, then the PPR or ‘real rice’ was only 61% of what it was in 1972, and therefore had lost 39% of its purchasing power, signifying that rice was relatively low in price.